Analisis Proses Penanganan Kapal Penumpang terhadap Ketepatan Waktu Jadwal Operasional Kapal - Aji Pandita Ratu Rukmantara; Vivian Karim Ladesi; Winoto Hadi; Siti Sahara; Kencana Verawati (IPM2KPE, 2024)
This research aims to analyze the process of handling passenger ships regarding the timeliness of ship operational schedules located at PT. Indonesian National Shipping Tanjung Priok Branch. The method used is a qualitative descriptive method with primary and secondary data where data collection uses observation and interviews to determine the population, sample, data collection, data processing and data compilation. The results of the research can be concluded that the estimated and actual schedule for ship arrival and departure does not match, the average time required for ship arrival is 01:43 (one hour and forty-three minutes) and for ship departure is 00:54 (fifty-four minutes). ) and the percentage of ships on schedule is only 12% or 2 times out of 17 operations. Delays are caused by weather factors, machine repairs, clearance processes and poor internet connections. Therefore, coordination between ship operations and ship crew as well as internet stability is a solution to the timeliness of ship operational schedules. Keywords: Passenger Ships, Punctuality, Ship Handling